Pengaruh Teknologi Informasi Terhadap Transformasi Digital dan Inovasi dalam Organisasi - Harefa, Fatarolius; Lase, Daniel Hasanema (CV. SINAR HOWUHOWU, 2025)
In the rapidly evolving digital era, information technology (IT) serves as the backbone of the digital transformation process experienced by organizations across various sectors. Digital transformation goes beyond technology adoption; it entails fundamental changes in how organizations operate, innovate, and interact with customers and other stakeholders. This article reviews the impact of IT on digital transformation and innovation within organizations, highlighting how IT contributes to enhancing operational efficiency, accelerating the development of new products and services, and enriching customer experiences. Additionally, it explores the main challenges organizations face when adopting new technologies, such as high implementation costs, shifts in workplace culture, and data security risks. This study aims to help organizations understand the essential role of IT in supporting innovation and maintaining competitiveness in a dynamic market.